An improved heuristic UTD solution for multiple-edge transition zone diffraction. - Tzaras, C. (IEEE Transactions on antennas and propagation)
This paper describes a new heuristic approach for multiple edge diffraction modeling based on the uniform theory of diffraction (UTD). It incorporates the slope diffraction terms which can be realized as a second-order diffraction process, vital for accurate predictions when more than one edge exists. The predictions of this approach are compared with the Vogler (1982) solution and were found to be in very good agreement for many different geometrical arrangements, with low computational complexity. The solution is also extended to wedge diffraction